2001
DOI: 10.1023/a:1011965826553
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract. The SNC (Shergotty-Nakhla-Chassigny) meteorites have recorded interactions between martian crustal fluids and the parent igneous rocks. The resultant secondary minerals -which comprise up to ~ 1 vol.% of the meteorites -provide information about the timing and nature of hydrous activity and atmospheric processes on Mars. We suggest that the most plausible models for secondary mineral formation involve the evaporation of low temperature (25-150 o C) brines. This is consistent with the simple mineralog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(41 citation statements)
references
References 97 publications
(114 reference statements)
1
37
0
1
Order By: Relevance
“…All of these samples are igneous rocks and show some degree of weathering, frequently in the form of carbonate minerals and in low abundance (1 % or less) (Bridges et al 2001). A strong case has been made that at least some of these samples contain carbonate that formed on Mars and thus preserve the chemical signatures of aqueous environments on that planet.…”
Section: Carbonates In Martian Meteorites/atmospheric Co Isotopesmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these samples are igneous rocks and show some degree of weathering, frequently in the form of carbonate minerals and in low abundance (1 % or less) (Bridges et al 2001). A strong case has been made that at least some of these samples contain carbonate that formed on Mars and thus preserve the chemical signatures of aqueous environments on that planet.…”
Section: Carbonates In Martian Meteorites/atmospheric Co Isotopesmentioning
confidence: 99%
“…The carbonates typically occur as small crystals (<100 µm) along cracks and within crushed zones of the rocks. They are sometimes associated with other aqueous alteration phases such as phyllosilicates, iron oxides, and iron sulfides (Bridges et al 2001). Bridges et al (2001).…”
Section: Chemistry and Petrography Of Carbonatesmentioning
confidence: 99%
“…Carbonates are widely predicted to occur because the main constituent of Mars' atmosphere is CO 2 and this dissolves readily in water, giving a solution from which carbonate can precipitate (Equation (1)). However, apart from in minor abundances in Martian meteorites (Bridges et al 2001), and in dust (Bandfield et al 2003), carbonates have not been observed in quantity at the Martian surface. Carbonate precipitation is highly dependent on the pH of the fluid in which CO 2 is dissolved.…”
Section: The Scientific Objectives Of Watsenmentioning
confidence: 97%
“…The rocks are all igneous, and the effects of water can be seen in some of the meteorites (Fig. 2), where two distinct types of alteration product can be found (Bridges & Grady 1999;Bridges et al 2001). One alteration product is exemplified by 'iddingsite ', a fine-grained mixture of the clay minerals smectite and illite, produced by the weathering along cracks within olivine grains.…”
Section: Water On Mars : Evidence From Meteoritesmentioning
confidence: 99%
See 1 more Smart Citation